Enzymatic labelling of snake venom phospholipase A2 toxins - Spolaore, Barbara (2019)
Almost all animal venoms contain secretory phospholipases A2 (PLA2s), 14 kDa disulfide-rich enzymes that hydrolyze membrane phospholipids at the sn-2 position, releasing lysophospholipids and fatty acids. These proteins, depending on their sequence, show a wide variety of biochemical, toxic and pharmacological effects and deserve to be studied for their numerous possible applications, and to improve antivenom drugs. The cellular localization and activity of a protein can be studied by conjugating it with a tag. In this work, we applied an enzymatic labelling method, using Streptomyces mobaraense transglutaminase, on three snake venom PLA2s: a recombinant neuro- and myotoxic group I PLA2 from Notechis scutatus scutatus, and two myotoxic group II PLA2s from Bothrops asper - one of them a natural catalytically inactive variant. We demonstrate that TGase can be used to produce active mono- or bi-derivatives of these three PLA2s modified at specific Lys residues, and that all three of these proteins, conjugated with fluorescent peptides, are internalized in primary myotubes.